2020
DOI: 10.1128/aem.02080-20
|View full text |Cite
|
Sign up to set email alerts
|

Competence-Stimulating-Peptide-Dependent Localized Cell Death and Extracellular DNA Production in Streptococcus mutans Biofilms

Abstract: Extracellular DNA (eDNA) is a biofilm component that contributes to the formation and structural stability of biofilms. Streptococcus mutans, a major cariogenic bacterium, induces eDNA-dependent biofilm formation under specific conditions. Since cell death can result in the release and accumulation of DNA, the dead cells in biofilms are a source of eDNA. However, it remains unknown how eDNA is released from dead cells and is localized within S. mutans biofilms. We focused on cell death induced by the extracell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 61 publications
0
15
0
Order By: Relevance
“…Recently, Nagasawa et al . [105] demonstrated that CSP may be involved into releasing eDNA in S. mutans biofilms, contributing to firmer and more stable S. mutans biofilms. Counterintuitively, S. gordonii mutants, lacking the comC gene, produced more eDNA and more stable biofilms in the presence of C. albicans than the isogenic wild-type counterpart [106] .…”
Section: The Oral Microbiome and The Oralomementioning
confidence: 98%
“…Recently, Nagasawa et al . [105] demonstrated that CSP may be involved into releasing eDNA in S. mutans biofilms, contributing to firmer and more stable S. mutans biofilms. Counterintuitively, S. gordonii mutants, lacking the comC gene, produced more eDNA and more stable biofilms in the presence of C. albicans than the isogenic wild-type counterpart [106] .…”
Section: The Oral Microbiome and The Oralomementioning
confidence: 98%
“…This was consistent with previous research 10,27 . Nucleic acids released into the extracellular environment by dead pathogens have been demonstrated to contribute to the formation and structural stability of BFs and provide abundant nutrients for live pathogens to support the sustainable growth of BFs 28 . This result suggested that over time, the number of dead cells at the bottom of the BFs increased, and the structure of the BFs became more stable and robust.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our studies, it appears that eDNA is also an important common factor. We demonstrated that 2D confinement offers the opportunity to test conditions that may otherwise be impossible to recreate in a controlled manner, which may reveal cell affinity for particular environmental geometries (Nagasawa et al, 2020b).…”
Section: Section 2: 2d Microfluidics Enable Imaging Of Edna Productio...mentioning
confidence: 99%
“…eDNA is an important component of the EPS matrix in S. mutans biofilms and is necessary for initial cell attachment; however, the mechanisms by which cells release eDNA from within a biofilm are unclear. By culturing S. mutans in our 2D microchambers, we imaged the release of eDNA into the extracellular space, which we were correlated with cell death (Nagasawa et al, 2020b) (Fig. 2D).…”
Section: Section 2: 2d Microfluidics Enable Imaging Of Edna Productio...mentioning
confidence: 99%
See 1 more Smart Citation